2014
DOI: 10.1002/alr.21294
|View full text |Cite
|
Sign up to set email alerts
|

Increase of high mobility group box chromosomal protein 1 in eosinophilic chronic rhinosinusitis with nasal polyps

Abstract: Upregulation of HMGB1 could be a significant marker typically in eosinophilic CRSwNP and it may also contribute to the pathogenesis of CRSwNP along with IL-5, IL-8, and TNF-α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
(67 reference statements)
2
26
0
Order By: Relevance
“…Available data indicated HMGB1 expression mainly in the inflammatory infiltrates (especially eosinophilic ones), not in epithelial cells [21]. Moreover, significant differences in the HMGB1 protein level as well as the messenger RNA levels of HMGB1 were found between non-eosinophilic CRSwNP and controls [29]. This observation is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Available data indicated HMGB1 expression mainly in the inflammatory infiltrates (especially eosinophilic ones), not in epithelial cells [21]. Moreover, significant differences in the HMGB1 protein level as well as the messenger RNA levels of HMGB1 were found between non-eosinophilic CRSwNP and controls [29]. This observation is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Another study [18] by our research group has recently confirmed the hypothesis that up-regulation of HMGB1 could be a significant marker of eosinophilic CRSwNP and contribute to the pathogenesis of CRSwNP along with IL-5, IL-8 and TNF-α (fig. 2).…”
Section: Hmgb1 and Rhinosinusitissupporting
confidence: 59%
“…RAGE may be required for HMGB1-mediated eosinophil activation (Curran and Bertics, 2011; Lotfi et al, 2009). Upregulation of HMGB1 contributes to the pathogenesis of eosinophilic chronic rhinosinusitis with nasal polyps (Chen et al, 2014b). …”
Section: Hmgb1 Functionmentioning
confidence: 99%